Sosialisasi Pengembangan dan Pengenalan Alat Bantu Sederhana Penyiraman Tanaman Otomatis di Desa Randuwatang - Nasrulloh, Muhammad Farid; Sujono, Sujono; Arifin, Muhyiddin Zainul; Hasannudin, Nur; Aris, Muhammad Ansori; Fatchulloh, Mohammad; Nasrullah, Muhamad Iqbal (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2024)
Unconsciously, in our daily lives, we often use various tools and technology to make our lives easier. Simple examples include automatic air fresheners and deodorizers to scent a room without having to spray it manually. The use of this technology is commonplace in this day and age which is full of technological innovation, and there are still many examples of the use of technology like the one above, especially in automating daily activities. In the agricultural sector, the internet of things can be used for the purpose of increasing much better results and maximizing time efficiency. Automatic plant watering is a modern watering technique without using human power as its main role. There are several problems faced by farmers and households in using technology to make work easier, especially in planting in Randuwatang village. Due to a lack of interest and knowledge about the use of this technology, especially for citizens or the general public. So we want to provide a solution to this problem by providing open lessons as well as practice in using tools in the form of automatic plant watering. The approach used in seminars introducing automatic plant watering is an educational or demonstrative approach. The implementation of an automatic watering system as part of a non-profit program in Randuwatan Village has given us a new understanding of the importance of technology in agriculture. This tool provides an effective solution to make watering plants easier, save energy and water, and optimize plant maintenance.